Optimization and evaluation of transdermal delivery system for nebivolol hydrochloride - Shelke, P V; Rachh, Punit R; Mankar, S D; Prasad L. Gorde (Creative Pharma Assent, 2024)
Background: Nebivolol hydrochloride, a β1-receptor antagonist known for its antihypertensive properties, boasts a plasma half-life of 10 hours and an oral bioavailability of 12%. In this study, we aimed to enhance the therapeutic effectiveness of Nebivolol hydrochloride and circumvent its extensive hepatic first-pass metabolism by developing transdermal matrix patches. Methodology: Utilizing Central Composite Design (CCD), nine formulations were devised, comprising Hydroxypropyl methylcellulose K15M and Eudragit S100 as independent variables, with 10% w/w triethyl citrate as the plasticizer. Key dependent variables were evaluated, including folding endurance, moisture content, tensile strength, in vitro drug release, and flux. Fourier transform infrared spectroscopy (FTIR) assessed the compatibility between the drug and polymer. Results and discussion: Among the formulations, FP8 demonstrated the highest drug release (85.88% over 24 hours), attributed to its elevated concentration of hydrophobic polymer. The optimized formulation was determined based on the results of dependent variables. Conclusion: These findings suggest that the developed matrix transdermal film holds promise as a potential candidate for sustained drug release over a 24-hour.